The relationships between OHS prevention costs, safety performance, employee satisfaction and accident costs. Issue 2 (3rd April 2017) - Bayram, Metin; Ünğan, Mustafa C.; Ardıç, Kadir
Abstract : Little is known about the costs of safety. A literature review conducted for this study indicates there is a lack of survey-based research dealing with the effects of occupational health and safety (OHS) prevention costs. To close this gap in the literature, this study investigates the interwoven relationships between OHS prevention costs, employee satisfaction, OHS performance and accident costs. Data were collected from 159 OHS management system 18001-certified firms operating in Turkey and analyzed through structural equation modeling. The findings indicate that OHS prevention costs have a significant positive effect on safety performance, employee satisfaction and accident costs savings; employee satisfaction has a significant positive effect on accident costs savings; and occupational safety performance has a significant positive effect on employee satisfaction and accident costs savings. Also, the results indicate that safety performance and employee satisfaction leverage the relationship between prevention costs and accident costs.